PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KERJA KARYAWAN PADA PT COCOA LAND BALI - Pebri Antara Yoga Nanda, I Gede; Mayasari, Ni Made Dwi Ariani (Universitas Pendidikan Ganesha, 2025)
This study aims to determine the influence of work discipline and work motivation on employee job satisfaction at PT Cocoa Land Bali, both partially and simultaneously. The research uses a quantitative approach with a survey method through a Likert scale questionnaire that has been tested for validity and reliability. The data were analyzed using classical assumption tests followed by multiple linear regression analysis. The results show that: (1) work discipline has a positive and significant effect on job satisfaction, (2) work motivation also has a positive and significant effect on job satisfaction, and (3) simultaneously, work discipline and motivation xhave a positive and significant effect on employee job satisfaction. These findings highlight the importance of managing work discipline and motivation to improve job satisfaction. Therefore, the company is advised to implement a consistent disciplinary system and provide continuous motivational support to optimally enhance employee job satisfaction.